2008
DOI: 10.1038/nmeth.1204
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward ladder sequencing of peptides using a Lys-N metalloendopeptidase

Abstract: We introduce a method for sequencing peptides by mass spectrometry using a metalloendopeptidase that cleaves proteins at the amino side of lysine (Lys-N). When analyzed by electron transfer dissociation (ETD)-based mass spectrometric sequencing, Lys-N-digested peptides that contain a single lysine residue produce spectra dominated by c-type fragment ions, providing simple ladders for sequence determination. This method should be a valuable strategy for de novo sequencing and the analysis of post-translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
140
1
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 14 publications
12
140
1
3
Order By: Relevance
“…Intrinsic to the ETD process is the loss of one proton through charge reduction. We have previously demonstrated that in a single proton scenario, the basic moieties influence which fragment ions will be observed (19,21). The proportion of c and z ions is dependent on the basicity present at each terminus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic to the ETD process is the loss of one proton through charge reduction. We have previously demonstrated that in a single proton scenario, the basic moieties influence which fragment ions will be observed (19,21). The proportion of c and z ions is dependent on the basicity present at each terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Using Lys-N, the majority of the proteolytic peptides contain a single N-terminal lysine residue and can be enriched by strong cation exchange (SCX) chromatography (20). These peptides generate predominantly sequence diagnostic "c" ion series upon ETD (19), resulting in easy to interpret sequence ladders, which opens up a unique avenue for de novo sequencing and, as we show here, markedly reduces the dependence on databases.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This approach would be valuable to distinguish modification by ubiquitin-like proteins (Ubls) versus conventional ubiquitination based on different C-terminal sequences. Also, proteolytic digests using Lys-N, which yield almost complete c-ion series in ETD, could be well suited for this purpose [44]. Finally, multiple-reactionmonitoring (MRM) [45] and "middle-down" mass spectrometry [46] are now also applied to the detection of protein ubiquitination, both of which could potentially benefit from being combined with ETD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, > 2 + peptide charge states during MS ionization frequently require a higher number of basic amino acids within the respective peptide. Therefore, alternate proteases such as Lys-C, Lys-N, or Arg-C have to be used (Taouatas et al , 2008 ), which nevertheless suffer from reduced specifi city and sequence coverage. Even disregarding further drawbacks such as lower fragmentation effi cacy in comparison to CID and prolonged fragmentation Figure 1 (A) Glycoprotein analysis can be divided into three tasks: elucidation of attachment sites (glycoproteomics), glycan profi ling and structural analysis (glycomics), and fi nally characterization of microheterogeneities.…”
Section: Techniques In Ms-based Glycosylation Site Assignmentmentioning
confidence: 99%